The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.ijantimicag.2020.106037
|View full text |Cite
|
Sign up to set email alerts
|

Ivermectin: repurposing a multipurpose drug for Venezuela's humanitarian crisis

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
(25 reference statements)
0
12
0
Order By: Relevance
“…A different observation on the process by which ivermectin inhibits the growth of mosquitoes when infected with P. falciparum [106]. Kobylinski et al [103] reported that ivermectin decreased the intensity and prevalence of oocyst in different mosquitoes, while de Carvalho et al and Perez-Garcia et al [104,107] reported a reduction in the prevalence of oocyst without affecting the intensity in mosquito infected with P. falciparum and P. vivax. Three different avermectins were also tested with respect to the hepatic effect of Plasmodium.…”
Section: Endectocides For Malaria Controlmentioning
confidence: 99%
“…A different observation on the process by which ivermectin inhibits the growth of mosquitoes when infected with P. falciparum [106]. Kobylinski et al [103] reported that ivermectin decreased the intensity and prevalence of oocyst in different mosquitoes, while de Carvalho et al and Perez-Garcia et al [104,107] reported a reduction in the prevalence of oocyst without affecting the intensity in mosquito infected with P. falciparum and P. vivax. Three different avermectins were also tested with respect to the hepatic effect of Plasmodium.…”
Section: Endectocides For Malaria Controlmentioning
confidence: 99%
“…[3]. While at nanomolar concentrations it is effective mostly against nematodes, at higher concentrations, multiple new targets were identified [4,5]. Activity against various types of cancer has been reported [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Whilst the world is witnessing a terrible humanitarian crisis in LATAM and the Caribbean with public health systems in complete chaos with an exhausted team of frontline workers, this could be a perfect scenario for promising drugs to attenuate the severe damages caused by COVID-19 [ 5 ]. Corsello et al [ 6 ] have put together an online drug-repurposing library that classifies a number of compounds from a built-in database.…”
mentioning
confidence: 99%